Nomenclatural corrections, neotype designation and new subspecies description in the genus Suiriri (Aves: Passeriformes: Tyrannidae) - Kirwan, Guy M.; Steinheimer, Frank D.; Raposo, Marcos A.; Zimmer, Kevin J. (Zootaxa, 2014)
Zimmer et al. (2001) documented two morphological and vocal forms within what was then known as Suiriri suiriri affinis, and described the short-billed form as Suiriri islerorum. However, studies of the Burmeister type material held at the Natural History Collections of the Martin-Luther-University Halle-Wittenberg, Germany, revealed the types of Suiriri s. affinis (Burmeister, 1856) to be the same taxon as Suiriri islerorum, which name therefore becomes a junior synonym. No published name is available for the long-billed form. A new name is therefore introduced by an original description in accordance with the International code on zoological nomenclature. The original type material of S. s. bahiae (Berlepsch, 1893) is confirmed to be lost; a neotype is designated.